Limited evidence for a positive relationship between hybridization and diversification across seed plant families. (1st August 2021) - Mitchell, Nora; Whitney, Kenneth D.
Abstract: Hybridization has experimental and observational ties to evolutionary processes and outcomes such as adaptation, speciation, and radiation. Although it has been hypothesized that hybridization and diversification are positively correlated, this idea remains largely untested empirically, and hybridization can also potentially reduce diversity. Here, we use a hybridization database on 170 seed plant families, life history information, and a time‐calibrated phylogeny to test for phylogenetically‐corrected associations between hybridization and diversification rates, while also taking into account life‐history traits that may be correlated with both processes. We use three methods to estimate diversification rates and two metrics of hybridization. Although hybridization explains only a small amount of overall variation in diversification rates, we show that diversification and hybridization are sometimes positively correlated, although the effect sizes are very small. Moreover, the relationship remains detectable when incorporating the correlations between diversification and two other life history characteristics, perenniality and woodiness. We discuss potential mechanisms for this association under four different scenarios: hybridization may drive diversification, diversification may drive hybridization, both hybridization and diversification may jointly be driven by other factors, or, as an alternative, that there is in fact no relationship between the two. We suggest future studies to disentangle the causal structure.